QUATERNARY GLACIAL-INTERGLACIAL CLIMATE CYCLES IN HAWAII - Sheldon N.D. (My University, 2006)
The upper kilometer of the Hawaiian Scientific Drilling Program core consists of lavas that were emplaced subaerially, burying paleosols. These paleosols were preserved with minimal alteration and are used to construct a ~330-kyr Quaternary climate record. Within the temporal resolution of this record, there appears to be a ~100-kyr climate oscillation between cool-dry and warm-wet conditions, indicating that tropical regions such as Hawaii have responded to the same global climate forcings as have higher-latitude areas during at least the past three glacial-interglacial cycles. It is also suggested that Hawaiian climate may have become progressively warmer and wetter over the same period. © 2006 by The University of Chicago. All rights reserved.
Keywords: Quaternary; Cenozoic::Quaternary; Четвертичный